Intergovernmental relations in the management of the COVID-19 pandemic: X-ray of habitat management in a federal setting (Greater Buenos Aires Agglomeration, Argentina) - M. M. Di Virgilio; M. P. Diaz; L. Ramírez (Ибероамериканские тетради, 2022)
In Argentina, during the year 2020, the National Government has implemented numerous and varied assistance, containment and promotion initiatives in key public policy sectors to respond to the crisis unleashed by the COVID-19 pandemic. Likewise, provincial and local governments launched their own initiatives to support those emanating from the central level and facilitate the implementation and adaptation of national initiatives in their territories. The citizens, for their part, have adapted to, used or resisted the guidelines and proposals of the executives of the different levels of government. The pandemic scenario (in its different phases) exposes the tension between a centralized logic - typical of the design of initiatives aimed at responding to an emergency - and multilevel governance at a time when it is impossible to ignored that crisis contexts, such as the one imposed by the COVID-19 pandemic, strongly stress the relations between the different levels of government and between these and the citizenry. In this context, this paper focuses on intergovernmental relations and examines the initiatives, devices and instruments mobilized by the different levels of government to respond to urban issues in general and housing needs in particular, in the pandemic context, focusing on the initiatives that had habitat and housing as a privileged axis of intervention. The work is based on the analysis of regulations and press material. It also draws on in-depth interviews with public officials and agents from different governmental levels. It presents the composition of the political organization of the Greater Buenos Aires Agglomerate and the political-institutional relations between thedifferent levels of government, as well as a characterization of the focal points for intervention, devices and instruments that made public interventions feasible (especially in the National Government, the Government of the City of Buenos Aires and the Government of the Province of Buenos Aires). To conclude, the paper focuses on territorially-based experiences in order to account for the initiatives from a bottom-up perspective.